2015
DOI: 10.7314/apjcp.2015.16.17.7583
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Anti-EBV IgG among Various Age Groups from Khon Kaen Province, Thailand

Abstract: Epstein-Barr virus (EBV) is an extremely common herpesvirus that may cause asymptomatic infection or various diseases, including infectious mononucleosis, certain lymphoproliferative diseases and several types of neoplasms. Vaccine development is an important strategy to reduce the burden of EBV-associated diseases and the timing of vaccinations should be before primary infection occurs. In the past, more than 90% of Thai children were infected with EBV in early childhood. Now, due to the improved healthcare s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 25 publications
5
27
1
Order By: Relevance
“…In our report, the pre‐transplant prevalence of EBV IgG seropositivity was as high as 86.5% in renal transplant recipients, was 66.7% in patients aged <5 years, and 88.2% in patients aged >5 years; thus, EBV IgG seropositivity appeared to increase until 6 years of age after which it plateaued, with a prevalence of 85–90% in Asian countries, except Japan . EBV infection tends to develop early in developing countries and in people with low socioeconomic statuses .…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In our report, the pre‐transplant prevalence of EBV IgG seropositivity was as high as 86.5% in renal transplant recipients, was 66.7% in patients aged <5 years, and 88.2% in patients aged >5 years; thus, EBV IgG seropositivity appeared to increase until 6 years of age after which it plateaued, with a prevalence of 85–90% in Asian countries, except Japan . EBV infection tends to develop early in developing countries and in people with low socioeconomic statuses .…”
Section: Discussionmentioning
confidence: 50%
“…recipients, was 66.7% in patients aged <5 years, and 88.2% in patients aged >5 years; thus, EBV IgG seropositivity appeared to increase until 6 years of age after which it plateaued, with a prevalence of 85-90% in Asian countries, except Japan. 8 EBV infection tends to develop early in developing countries and in people with low socioeconomic statuses. 9,10 In contrast, the rate of EBV IgG positivity tend to be lower in patients in developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the consistency of these two tests was 95.7% (Table ). Furthermore, through a literature review, we found that the positive rate of EBV‐VCA worldwide varied based on ethnicity and country and was relatively high in Thailand but low in America . In Thailand, the positive rate of EBV‐VCA IgG was more than 90% in childhood, reaching 100% in adults over 40 years of age.…”
Section: Discussionmentioning
confidence: 93%
“…In areas of comparable endemicity, approximately 40% of children under the age of five years have been reported to have circulating antibody against the parasite 21 , suggesting that women of child bearing age have high levels of circulating IgG available for transplacental transfer to foetal circulation. In the case of EBV, there is strong evidence from different parts of the world that infection is generally acquired within the first few years of life and that up to one in three children are EBV-seropositive by the age of five years [22][23][24][25] . This early exposure profile suggests that the widespread recognition of EBV antigens in this study could be traced to a combination factors including responses to natural infection as well as passively acquired maternal antibody as a result of long-term maternal exposure.…”
Section: Discussionmentioning
confidence: 99%